A Study on Ecology of Amphibians breeding habitats of Kokrajhar District, Assam, India - Narzary, Jwngma (International Journal of Scientific Research in Biological Sciences, 2020)
Amphibians generally have a biphasic life cycle. They complete their development stages in water. The time taken for a tadpole from egg to reach metamorphosis varies from weeks to month and depends upon a number of factors. Water temperature is an important factor as it influences feeding rate, size, and metamorphosis and growth rate of a tadpole. Water quantity and water quality are also important factors for the development of tadpoles. Water quality parameters directly influence biotic components present in the habitat. Of biotic components planktons determine the availability of food in the ecosystem. In the present study certain water quality parameters and some planktons were recorded from the habitats of Kokrajhar district, Assam, India (89.46′E to 90.38′E longitude and 29.19′N to 26.54′N latitudes).